Improving quality of components and protein preparations of blood plasma by introduction of quality management according to the principles of GMP and ISO 9001 in the blood service institutions with benchmarking effectiveness. - Liubchack, V. V.; Timchenko, A. S.; Liubchack, V. A. (Medicni Perspektivi, 2014)
Aspects of harmonious introduction of the new standards of quality management in the institutions of blood service were considered. It was proved that it does not contradict to current legislation and significantly increases pathogenic security of blood components and blood products.